The Community Work of the Physical Theraphy of the Students for the Elderly - Banogon, Mitchelle T. (Silliman Journal, 2022)
The community work of the Physical Therapy students not only provided health care services to rural people, but also increased their understanding of the significance of physical therapy. Their community activities included assessing the baseline vital signs and physical capability of the elderly, providing low impact aerobic exercises, conducting disability survey, and initiating community-based rehabilitation of disabled persons along with their family members. Results of this community work showed changes in the attitude and values of the students and the development of expertise among them despite the short period of their work with the community.